Evaluation of surrogate markers for human immunodeficiency virus infection among blood donors at the blood bank of "Hospital Universitário Regional Norte do Paraná", Londrina, PR, Brazil - Reiche Edna Maria Vissoci; Vogler Ingridt Hildegard; Morimoto Helena Kaminami; Bortoliero André Luis; Matsuo Tiemi; Yuahasi Kátia Kioko; Cancian Sanderson Júnior; Koguichi Roberto Setsuo (Universidade de São Paulo (USP), 2003)
This study evaluated the usefulness of the anti-HBc, hepatitis C virus antibodies (anti-HCV), human T cell lymphotropic virus I and II antibodies (anti-HTLV I/II), serologic tests for syphilis, and surface antigen of hepatitis B virus (HBsAg) as surrogate markers for the risk for HIV infection in 80,284 serum samples from blood donors from the Blood Bank of "Hospital Universitário Regional Norte do Paraná", Londrina, Paraná State, Brazil, analyzed from July 1994 to April 2001. Among 39 blood donors with positive serology for HIV, 12 (30.8%) were anti-HBc positive, 10 (25.6%) for anti-HCV, 1 (2.6%) for anti-HTLV I/I, 1 (2.6%) was positive for syphilis, and 1 (2.6%) for HBsAg. Among the donors with negative serology for HIV, these markers were detected in 8,407 (10.5%), 441 (0.5%), 189 (0.2%), 464 (0.6%), and 473 (0.6%) samples, respectively. The difference was statistically significant (p < 0.001) for anti-HBc and anti-HCV. Although the predictive positive value for these surrogate markers were low for HIV infection, the results confirmed the anti-HBc and anti-HCV as useful surrogate markers for HIV infection thus reinforcing the maintenance of them in the screening for blood donors contributing to the prevention of the small number of cases in which HIV is still transmitted by transfusion.